Prospects for Development of Highly Satiating Foods in Poland - Skotnicka, Magdalena; Kłobukowski, Filip; Śmiechowska, Maria (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2017)
The high level of competition between food products on the market has encouraged the development of various types of functional foods. Consumer demands and requirements for both medicinal and healthy products has caused food manufacturers to widen their product offerings. The objective of this study was to present the legal status of functional food production and sales, as well as analyse the possibilities of developing customized foods, in particular, highly satiating foods. In this time of obesity epidemic, the use of specifically designed food products which suppress hunger and give the feeling of satiety could be an effective tool in preventing obesity and controlling body mass. There is an optimistic prognoses that this type of food will be introduced on the Polish market.